Earlier Response Assessment in Invasive Aspergillosis Based on the Kinetics of Serum Aspergillus Galactomannan: Proposal for a New Definition - Nouér, Simone A. (Oxford University Press, 2011)
Background. Current criteria for assessing treatment response of invasive aspergillosis (IA) rely on nonspecific subjective parameters. We hypothesized that an Aspergillus-specific response definition based on the kinetics of serum Aspergillus galactomannan index (GMI) would provide earlier and more objective response assessment. Methods. We compared the 6-week European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) response criteria with GMI-based response among 115 cancer patients with IA. Success according to GMI required survival with repeatedly negative GMI for ≥2 weeks. Time to response and agreement between the 2 definitions were the study endpoints. Results. Success according to EORTC/MSG and GMI criteria was observed in 73 patients (63%) and 83 patients (72%), respectively. The GMI-based response was determined at a median of 21 days after treatment initiation (range, 15–41 days), 3 weeks before the EORTC/MSG time point, in 72 (87%) of 83 responders. Agreement between definitions was shown in all 32 nonresponders and in 73 of the 83 responders (91% overall), with an excellent κ correlation coefficient of 0.819. Among 10 patients with discordant response (EORTC/MSG failure, GMI success), 1 is alive without IA 3 years after diagnosis; for the other, aspergillosis could not be detected at autopsy. The presence of other life-threatening complications in the remaining 8 patients indicates that IA had resolved. Conclusions. The Aspergillus-specific GMI–based criteria compare favorably to current response definitions for IA and significantly shorten time to response assessment. These criteria rely on a simple, reproducible, objective, and Aspergillus-specific test and should serve as the primary endpoint in trials of IA.